A green route to the synthesis of highly porous activated carbon from walnut shells for mercury removal - Hania Albatrni (17092945) (2024)
Activated carbon with a high surface area was synthesized using walnut shells with the objective of removing mercury ions. The procedure involved the utilization of potassium carbonate as the chemical activator. The porous material obtained was subjected to characterization using X-ray diffraction (XRD), scanning electron microscopy (SEM), Raman spectroscopy, energy-dispersive X-ray spectroscopy (EDX), Brunauer-Emmett-Teller (BET) analysis, and X-ray photoelectron spectroscopy (XPS). The BET surface areas obtained in this study reach up to 1046.9 m2/g, whereas the pore volumes range up to 0.665 cm3/g. Additionally, the findings indicate that the utilization of K2CO3 for chemical activation leads to the formation of a mostly amorphous structure. The present study aimed to evaluate the impact of several factors including mass dosage, pH, initial concentration of mercury, temperature, and contact time, on the efficiency of mercury removal. It was observed that the adsorption process exhibited spontaneity, endothermicity, and an increase in entropy. At a temperature of 35 °C, the adsorbent had a maximum adsorption capacity of 182.9 mg/g. The mechanism of adsorption involves the participation of ion exchange and electrostatic attractions, which combine synergistically to facilitate the process. This highlights the significance of both chemical and physical adsorption in the overall phenomenon. Other Information Published in: Journal of Water Process Engineering License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jwpe.2024.104802